Spatial rain database in Africa - (:unkn) unknown (My University, 2019)
Our research project aims to develop a method for exploiting global rainfall products (satellite rainfall or rainfall from meteorological reanalyses) for use in extreme flood estimation studies in poorly or poorly gauged watersheds in Africa. Indeed, in regions with low rainfall data, global precipitation reanalysis products can be a valuable source of rainfall information for hydrological applications, especially since the spatial (a few hundred km2) and temporal (daytime) resolutions of the reanalysis data sets are compatible with those of hydrological models.
Keywords: African Research